Struktur Alur dalam Novel Pulang-Pergi Karya Tere Liye dan Relevansinya Terhadap Pembelajaran Sastra - Wahyuli, Indah; Azis, Azis; Asri, Aswati (TITIK DUA: Jurnal Pembelajaran Bahasa dan Sastra Indonesia, 2024)
This study aims to describe the plot structure in the novel Pulang-Pergi by Tere Liye and its relevance to literature learning in junior high school. The research method the author uses is descriptive; the form of this research is qualitative; and it uses a structural approach. The results show that there is more than one conflict contained in the novel Pulang-Pergi by Tere Liye, namely the conflict between Bujang and his friends with Natascha and his troops on Bujang and Maria's wedding night due to Natascha's past grudges with Otets, with hitmen, and with military members. All these conflicts are reduced to one main conflict, namely the togetherness and trust of Bujang and his friends in fighting Natascha's cruelty. Furthermore, the main climax that is able to summarize the story structure is marked by the urgency and inability of the characters to fight Natascha, Black Widow, and Diego (Natascha's ally). The novel Pulang-Pergi by Tere Liye can be relevant in junior high school grade VIII in the independent